Optimization Of Flameless Cyclone Combustion Chamber For The Combustion Of Biomass Producer Gas - Razak, Abang Muhammad Farith (Universiti Sains Malaysia, 2022)
Due to its low heating component, producer gas (PG) combustion results in flame instability, a slow burning rate, and a decrease in power production. A possible combustion method for enhancing combustion performance is flameless combustion. Its use with PG is still far less widespread, though. This work uses the data gathered from the existing experiment and numerical analyzation to study the reaction of the PG in Premixed Flameless Combustion. The Flameless Combustion produced with dilution ratio, R dil > 0.6 of the reactant. Multiple combustor with different nozzle air inlet diameter and combustor were created using SOLIDWORK software. The value for the parameter (air inlet nozzle diameter & combustor height) are 30 mm, 40 mm, 50 mm and 500 mm, 600 mm, 700 mm respectively. The purposed was to study the effect of the combustor parameter which combination will produce most optimum and efficient based from the Nitrogen Oxide (NOx) emissions also presence of the complete combustion. The data gathered from the Computational Fluid Dynamic (CFD) simulation by utilizing ANSYS Fluent software. Then, for the optimization of the cyclone combustor parameter, Minitab software were used by using Design of Experiment (DOE) concept which Full Factorial concept. Full factorial optimization using two factors—nozzle diameter and combustor height—and three stages produced a total of 9 data sets to analyze in the DOE concept. Based on the optimization's results, the data sets that have the most optimum results will be achieved.